Arteriovenous fistulas thrombosis in hemodialysis patients with COVID-19. Issue 3 (May 2022) - Desbuissons, Geoffroy; Michon, Arthur; Attias, Philippe; Burbach, Maren; Diaconita, Mirela; Karie-Guiges, Svetlana; Novelli, Luigi; Abou Rjeili, Marawa; Awad, Sameh; Besse, Francis; Viglietti, Denis; Beaudreuil, Severine; et al.
Background: The current Coronavirus disease 2019 (COVID-19) outbreak is associated with significant mortality, especially in patients suffering from end stage renal disease (ESRD) and hemodialysis patients. Several previous studies reported an over-risk of arterial and venous thrombosis, in particular pulmonary embolism and venous thrombosis of catheter in COVID19 patients in intensive care unit. However, arteriovenous fistula (AVF) thrombosis has rarely been reported yet in these patients. AVF thrombosis is a serious complication that impacts significantly patients outcome. Here, we aim to describe characteristics and prognosis of a cohort of COVID-19 hemodialysis (HD) patients presenting with AVF thrombosis. Methods: In the Ile de France region (Paris area) during the March 11th–April 30th 2020 period, fistula thrombosis cases were collected among COVID-19 hemodialysis patients in seven dialysis units and in interventional vascular departments. These patients' characteristics were analyzed through a review of the patient's medical records. Results: Seventeen patients were included in our study (median age 69 years). Ten patients (59%) were men. Ten patients (59%) were diabetic and 88% had a high blood pressure. The mortality rate in these patients was 47%. All thrombosis treated with a declotting procedures (64%) were successfully cleared, but with early relapse in 36%. Conclusion: Our study highlights AVF thrombosis as a severe complication in COVID-19 hemodialysis patients that contributed to the severity and accelerated death.